Fitness training in functional preparedness of highly qualified football players - Lisenchuk, G.; Leleka, V.; Bogatyrev, K.; Kokareva, S.; Adamenko, O.; Shchekotylina, N.; Romanenko, S.; Krupenya, S. (Journal of Physical Education and Sport, 2023)
In football, the task of improving the functional preparedness of highly qualified football players requires the use of special modes of training work, which has little connection with the system of special exercises for football players. Research hypothesis: innovative fitness techniques of functional training of football players will increase the level of their functional state, long-term maintain the necessary conditions during the two competitive periods of the annual training cycle, and thus contribute to a high final result of competitive activities. The objective of the research is to increase the functional conditions of highly skilled football players in the preparatory period of the annual macrocycle by means of fitness training. Participants: The study involved 25 players of FC "Zorya" (Luhansk city) aged 20 to 30 years. Methods: the submaximal bicycle ergometric test PWC170. The absolute value of the total physical working capacity (aPWC170) and the relative value of the total physical working capacity (rPWC170), the absolute value of the aerobic capacity - maximum oxygen consumption (aMOC) and the relative value of the aerobic capacity (rMOC) were calculated. Results: An experimental program of physical training of highly qualified football players has been developed, the feature of which was the use of three innovative methods of modern fitness training: MAX®, Tabata, HIIT. Statistically significantly better indicators of physical work capacity of football players have been registered in the formative experiment at the end of both preparatory periods of the 2019/2020 season compared to the corresponding periods of the 2018/2019 season - by 21.7% and 24.1% (p <0.001) and aerobic capacity - by 13.7% (p <0.001) and 10.9% (p <0.01); at the end of competitive periods - indicators of physical work capacity by 24.2% and 30.6% (p <0.001) and aerobic capacity - by 15.8% and 15.9% (p <0.001). Conclusions: The introduction of an experimental program with the use of fitness training innovative means in the training process of highly qualified football players of FC "Zorya" (Luhansk city) improved their physical performance and aerobic capacity. The effectiveness of the program was confirmed by the team of FC "Zorya" winning bronze medals in the championship of the Ukrainian Premier League of the 2019/2020 season.